Tietämyksen tehokas jakaminen: Datan ja Analytiikan wikisivun kehittäminen organisaatiossa - Mattsson, Erik (2024)
Information management and wiki technologies in organizations have been in use for several years. Often, only experts in the field process and refine data, even if the use of data would benefit many different experts. The unfamiliarity of data concepts in organizations can therefore make it difficult to use them effectively. This research was carried out as a development-style design study for the target organization and resulted in the creation of an artefact. Artefact is an open wiki platform that utilizes existing technologies. Its purpose is to make data and related topics transparent so that they are no longer unknown among different stakeholders. The artefact was built using cases from the literature review, the eDSR framework, user interviews, survey, development team meetings, and existing technologies. As key findings, the study found that wiki technology was the right tool for centralized data management for data concepts. The results clearly indicated that different user groups were satisfied with the application and wiki technology could also be used in other functions within the organization in the future. However, although the application is simple in structure, training was seen as necessary. Based on the results, an increase in the efficiency of the organization was observed both in the quality of the work and in terms of time. Research is topical in the growing world of information management, and research can benefit most organizations who want to improve their own organization's data concepts or data management.